Interleukin‐1‐β gene, but not the interleukin‐1 receptor antagonist gene, is associated with graves' disease - Chen, Rong‐Hsing (J Clin Lab Anal, 2005)
Interleukin‐1 (IL‐1) is considered to be involved in the pathogenesis of Graves' disease. The aim of this study was to test whether the IL‐1‐β gene promoter region and exon 5 and IL‐1 receptor antagonist (IL‐1Ra) gene intron 2 polymorphisms could be useful genetic markers for susceptibility to Graves' disease. A normal control group of 163 healthy people and another group of 95 patients with Graves' disease were examined. Polymerase chain reaction (PCR) was used to analyze the variable number of tandem repeats (VNTRs) at intron 2 of the IL‐1Ra gene for the polymorphism. PCR‐based restriction analysis was done for the IL‐1‐β gene polymorphisms of the promoter region and exon 5 using endonucleases AvaI and TaqI, respectively. We found significantly increased frequencies of the C/C homozygous genotype (χ(2) test, P=0.038; odds ratio (OR)=2.558, 95% confidence interval (CI)=1.205–5.430) and the C allele (χ(2) test, P=0.011; OR=1.589, 95% CI=1.094–2.309) in the IL‐1‐β gene promoter (−511 C/T polymorphism) in Graves' disease patients compared to normal controls. There were no significant differences in polymorphisms of IL‐1‐β gene exon 5 and IL‐1Ra gene intron 2 between the patient and normal control groups. A subgroup analysis also demonstrated no association between the severity of the disease and any polymorphism of IL‐1‐related genes. We suggest that the IL‐1‐β gene promoter polymorphism can be used as a genetic marker for susceptibility to Graves' disease. It is worthwhile to study the cytokine genes further because of the association between cytokines and Graves' disease. J. Clin. Lab. Anal. 19:133–138, 2005. © 2005 Wiley‐Liss, Inc.